Mental health literacy among Jordanian nurses: a cross-sectional study and scale validation - Walid Al-Qerem; Anan Jarab; Judith Eberhardt; Fawaz Alasmari; Alaa Hammad; Amani Moh’d Ibrahim Alfarajat; Sarah Abu Hour; Lujain Al-sa’di; Rama AlKhateeb; Walaa Ashran (BMC Nursing)
Abstract Background Mental health literacy (MHL) is critical for recognizing, managing, and preventing mental health disorders. Despite nurses’ pivotal role in patient care, their level of mental health literacy (MHL) in Jordan remains underexplored. This study aimed to assess MHL among Jordanian nurses and validate the Jordanian version of the Mental Health Literacy Scale (Jor-MHLS) for use in healthcare settings. Method This cross-sectional study was conducted at four major hospitals in Jordan: a university hospital, a military hospital, a governmental hospital, and a private hospital. A convenience sampling method was used to recruit nurses. Participants completed an Arabic version of the 27-item Jor-MHLS, which had been previously validated for the general population. The questionnaire was administered via electronic devices, either using a researcher-provided tablet or participants’ own devices. Confirmatory Factor Analysis (CFA) and Rasch analysis were performed to assess the scale’s validity and reliability, while quantile regression examined sociodemographic associations with MHL scores. Results The study included 429 nurses. The median MHL score was 60 out of 100, indicating moderate literacy levels. Nurses with ≤ 5 years of experience had significantly higher MHL scores than those with > 20 years. CFA validated the four-factor model with satisfactory fit indices (χ²/df = 3.1, RMSEA = 0.07, CFI = 0.92). Rasch analysis confirmed proper item hierarchy and no significant gender-based differential item functioning. Cronbach’s α values exceeded 0.70 across all factors, supporting the scale’s reliability. Conclusions The findings suggested moderate MHL levels among Jordanian nurses and highlight the need for targeted educational interventions and stigma reduction programs to enhance MHL. The validation of the Jor-MHLS confirmed its utility as a robust tool for assessing MHL in healthcare contexts. Future studies should explore longitudinal interventions to address gaps and improve outcomes. Clinical trial number Not applicable.